The Effect of profitability, investment opportunity set and free cash flow on dividends paid to companies, (Empirical Study of Manufacturing Companies): The Effect of profitability, investment opportunity set and free cash flow on dividends paid to companies, (Empirical Study of Manufacturing Companies) - Ari Lestari (Jurnal Mantik, 2020)
This study has the objective to find out how the effect of profitability, investment opportunity set and free cash flow to the payment of dividends on manufacturing companies listed in Indonesia Stock Exchange (BEI). The period used in this study is three years ie from 2013 - 2016. The approach taken by the authors using quantitative methods.This study uses secondary data obtained from the web www.idx.co.id, The analysis used in this study were using multiple linear regression were used to examine the effect of independent variables on a population of 141 dependen.Dari variable manufacturing company acquired eight manufacturing companies in the sample with a four-year observation period (2013-2016). The results showed that: Partially independent variables (1) Profitability effect on the payment of dividends, (2) investment opportunity set does not affect the payment of dividends, (3) Free cash flow does not affect the payment of dividends. Simultaneous (together) independent variables (profitability, investment opportunity set and free cash flow toward dividend payments.